IMPROVEMENT LAYOUT AND ELEMENTS WORK IN ERGONOMIC ASPECTS - Beci Sariani; Meizul Zuki; Yusril Dany (Jurnal Agroindustri, 2012)
The purpose of this study is to describe layout and elements of the movement labor, determine cake making job completion time before and after repair, complaints of pain workers and recomendation improved layout and elements work in ergonomic aspects. Layout and elements of the cake making job is less visible than ergonomic working conditions with temperatures as high as 290C and 300C, total distance moving much material for the production namely 2407 cm, manufacture molen 180 cm, 2926 cm baking and packaging 626 cm. Percentage of use right and left hand at creation pia cake is 50.11% and 54.4%. Making molen is 100% and 76.69%. Pia cake making is 12.76% and 12.21%. Packaging is 100% and 84.8%. Cycle time, normal time and standard time of content creation, namely 17004.15, 18.534.52 and 25.577.64 seconds (2 basins). Making molen is 560.23, 616.25 and 751.82 seconds (1 basin). Pia cake making is 1.165,45, 1314.63 and 1.603,85 seconds (2 trays), and packaging is 15,40, 16,79 and 23.17 seconds (2 pack). The application of ergonomics : 8 types of grievances felt a bit sick and 1 type of grievances felt sick. Station molen manufacture, workers felt no pain. Baking station pia (sub-stations) only complaint molen rolling on his back felt a little sore. Sub-station charging only 3 workers who feel a little pain complaints and pain. In the sub-station : 6 types pengovenan grievances felt a little sick. The packing station after repairs only felt a little pain in the waist